Body metamorphoses in digital fashion context - O. O. Pertel (Шаги, 2024)
The article is devoted to the study of hybrid images in digital fashion, to which the concept of “metamorphoses” can be applied. Using the concept of “metamorphoses” both form and content of visual objects are analyzed simultaneously, which corresponds to the idea of overcoming binarity, namely philosophical essentialism in relation to the concept of the human body and human subjectivity. Instead of a unitary subject, we propose an “expanded” vision of the human being as undergoing constant transformation depending on the internal and external environment. The philosophical justification for this position is based on the notion of “becoming” by Gilles Deleuze and Felix Guattari, as well as the concept of “metamorphoses” by Rosi Braidotti. The author also refers to Ovid’s poetic work of the same name as a primary source of the idea of metamorphoses and as a collection of myths that inspire designers around the world. The article examines images-metamorphoses of digital designers and brands such as The Fabricant x Trs.Mnz, Bad Binch TONGTONG with XTENDED IDENTITY, Tribute, Eva Iszoro, Antoni Tudisco, etc. They have become famous thanks to their placement on recognized digital clothing markets such as The Fabricant, The Dematerialized, and participation with digital shows in official fashion weeks. The author concludes that the concept of metamorphoses is a visual and methodological tool that permits one to analyze the relationship between man, animal, and machine. Metamorphoses are not only a way to represent the diversity of bodies, but also an occasion for discussion regarding aesthetics, politics and ethics from the point of view of these bodies.